TINGKAT KEPUASAN PETERNAK AYAM BROILER TERHADAP POLA KEMITRAAN MODEL CONTRACT FARMING DI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR (STUDI KASUS PT. MITRA ANUGERAH SATWA) - Yulida, Roza; ', Juherdi; ', Cepriadi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aims to determine are: (1) the characteristics of livestock enterprises PT. Mitra Anugerah Satwa, 2) a partnership PT. Mitra Anugerah Satwa, 3) plasma levels of satisfaction broiler breeder on PT. Mitra Anugerah Satwa. This type of research is descriptive using quantitative and qualitative data. Data collection is an interview conducted using questionnaires. Analysis of the data used is Costomer satisfaction index and the Importance of performance analysis. The characteristics of livestock enterprises PT. Mitra Anugerah Satwa was from 4000- 7000 scale tail and was using its own enclosure, in partnership with the company for one year, as well as per period income in the range of Rp. 8700000-15000000. Pattern-run partnership is core plasma model contract farming. Where the company became the nucleus and breeder becomes plasma that is closed. This study used seven variables to determine the level of satisfaction plasma farmers. After calculation using the Customer Satisfaction Index Customer Satisfaction Index value obtained was 80.74. If this value is based on the satisfaction index of plasma ranch, then the value of partnerships breeder Customer Satifaction Index plasma reached 0.81 and are in the interval from 0.81 to 1.00 so that it can be said that the overall satisfaction index of plasma farmers for variables tested are the criteria very satisfied. On the Importance analysis of performance analysis variables that have low performance is the quality of the livestock production facilities given company does every period of good quality and at a contract price of livestock production facilities are expensive. Keywords : Broiler, Contract Farming, Partnership, Satisfaction